Experimental Determination of Atomic Scale Structure and Energy-Level Alignment of C60 on CsPbBr3(001) - Loh, Hannah; Raabgrund, Andreas; Schneider, M. Alexander (ACS nano, 2025)
The efficiency and stability of perovskite solar cells are largely determined by the interfaces between different functional layers in the device. Here, we investigate the atomic scale structural and electronic properties of C60 on thin films of CsPbBr3 on Au(001) by scanning tunneling microscopy and spectroscopy (STM/STS). By varying the PbBr2 content of the film, we control the surface termination, switching between CsBr and PbBr2, with each exhibiting distinct reconstructions. Investigating the self-assembly of C60 in the submonolayer regime, we find that the molecule-substrate interaction is enhanced on the PbBr2-terminated perovskite film. By STS, we determine the electronic energy-level alignment of the C60 frontier orbitals, revealing that regardless of surface termination, a C60 film functions as an electron transport layer in a device. However, different surface terminations induce a significant shift in the molecular energy levels by 0.4 eV, with implications for electron mobility and recombination losses in applications.
CRIS-Team Scopus Importer:2025-03-21
Keywords: energy-level alignment; fullerene; perovskite; scanning tunneling microscopy; solar cell materials